The effects of investments in information technology on firm performance - Wong, Jeffrey; Dow, Kevin E. (IGI Global, 2011)
Analyzing the bene cial effects of investments in information technology (IT) is an area of research that interests investors and academics. A number of studies have examined whether investments in IT have a positive effect on some measure of earnings or other form of nancial return. Results from these studies have been mixed. This paper extends the literature by adopting an investor’s perspective on rm performance when IT invest- ments are made, using the preservation of capital as a performance measure. The authors examine companies that made public announcements of their investments in technology to see if they were able to mitigate losses to investors by reducing their downside risk to investors. This study further discusses whether different types of IT investments have different impacts on rm risk from an investor’s viewpoint. Findings suggest that IT investments impact a rm’s downside risk, and the authors offer an alternative perspective on the bene ts of IT investments, particularly where no positive incremental nancial results are evident.